BUILDING HUMANISTIC EDUCATION IN LEARNING: IMPLEMENTATION OF THE CONCEPT OF TEACHER PERSONALITY ACCORDING TO AL-ZARNUJI - Mawardi, Mawardi; Marduati, Marduati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
This study discusses the concept of teacher personality according to Al-Zarnuji and its relevance in building humanistic and inclusive education in learning. Al-Zarnuji identified six main characteristics that a teacher must have, namely sincere intentions, compassion, consistency in learning, avoiding envy, avoiding conflict, and avoiding hostility. These characteristics are an important foundation in forming a conducive learning environment and increasing student learning motivation. This study uses a qualitative approach with a descriptive-analytical method through a literature study of the book Ta'lim al-Muta'allim and contemporary Islamic education literature. The results of the study show that teacher personality has a significant impact on the formation of student character, especially in moral, social, and intellectual aspects. In the context of modern education, Al-Zarnuji's concept remains relevant to face the challenges of globalization in the digital era, where teachers are required to not only have academic competence, but also to be role models for their students. By instilling the values of sincerity, compassion, and patience, a teacher can create a humanistic learning environment in an effort to support the holistic development of students.